塑-钢齿轮传动装置在核电站鼓型旋转滤网的应用 - 朱荣生; 王秀礼; 曹新智; 燕浩; 胡志强 (Jixie chuandong)
Drum-like rotating filter net,which is the main filter device of nuclear power plant circular water system is driven by electromotor through gear wheels,the smaller one linked the bigger one with the electromotor.Sundries in water are filtrated by the filter board in drum-like rotating filter net to insure the pump and heat transformation device following it working order.The reasons of hardly abrasion between gear wheels is analyzed,and the driven manner between gears is improved.Result shows that the improved driven gears can totally satisfy working and repair cycle requirement.